PERENCANAAN SISTEM KELISTRIKAN ALAT WATER TREATMENT POLTEKAD - Dikara, Chandra Surya; Loemou, Willem; Setiawan, Wawan (Pustaka Poltekad, 2025)
This study focuses on the electrical system of water treatment equipment at Poltekad to ensure efficient water processing. Using a quantitative data-based experimental method, key variables such as electrical components, total power, and equipment usage duration were measured. The results show that the pump resistance is 353.2258 ?, with an input current of 0.62 Ampere and a power requirement of 135.78 Watts. The energy consumed by the equipment over three hours of daily use is 407.34 Wh. A 60 Ah, 12 Volt battery is recommended to meet the power demand during operation. The total system resistance is 4771.004 ?, with a total current of 1.12 A and total power of 162.38 Watts. This research not only ensures efficient equipment operation but also contributes to the development of water treatment technology, optimizing water resource utilization to meet community needs.